Study of the nutritional and health status of children with kidney failure and its impact on growth - El Ogrban ازدهار; Almadani اماني (Journal of Pure & Applied Sciences, 2024)
The study aimed to find out the effect of the diet of children with kidney failure who frequent visit Tripoli Medical educational Hospital on their growth and to identify the preventive ways to be Gfollowed through a balanced diet for cases of children with kidney failure. Fourth children were participated in this study. Fifteen of them they were healthy and did not suffer of any diseases and they were conducting periodic analysis in the hospital, their ages ranged between 5-15 years. Whereas, 25 of them were suffering of kidney failure and aged between 3.5-15 years and underwent regular dialysis in the pediatric dialysis unit at Tripoli University Medical Hospital, Libya – Tripoli. Height (m), weight (kg) and BMI (kg/m2) of the samples were measured. Moreover, the periodic analyzes, pathological, and therapeutic data for each patient were also recorded. Their diet were evaluated through a direct questionnaire filled by the patients or their companions. The collected data were analyzed by using the statistical analysis program (SPSS). The results of the study showed that height for sick children (19.86±119) was the most affected measurement compared to weight (6.98±25.05) and BMI (6.43±19.25), in comparison to the healthy children, since their average height was 17.68±142.40, average weight (11.96± 37.13) and average body mass index (17.68±1.81). A non-significant decrease in hemoglobin, vitamin D, and calcium measurements were also found in the chronic renal failure patients, when compared to healthy ones. On the other hand, there is a significant increase in parathyroid hormone and a significant decrease in protein among patients with chronic renal failure compared to the healthy ones. The results also showed that most children with kidney failure suffered of high pressure and high parathyroid hormones. The results also displayed that 40% of the total children consume less than 3 meals per day, and 40% of them consume between 3-5 meals.